Inhibitors of Human Dihydrofolate Reductase: A Computational Design and Docking Studies Using Glide - Lingala Yamini; Manga Vijjulatha (E-Journal of Chemistry)
Dihydrofolate reductase (DHFR) plays a vital role in the DNA synthesis by reducing dihydrofolic acid to tetrahydrofolic acid which is an essential component. Synthetic ligands like methotrexate (MTX), aminopterin (AMP) and their analogues act as potential anti metabolites by mimicking the coenzyme dihydrofolic acid (DHFA) they inhibit the activity of DHFR antagonistically. Several ligands which are similar to MTX analogues and 6, 8 substituted 2 – naphthyls (NAP) which can mimic the pteridyl group of DHFA have been computationally designed. These ligands were proposed to hinder the formation N5, N10 methylene tetrahydrofolic acid (THFA) coenzyme, which is essential for the DNA synthesis. The docking studies were done using grid, generated with the 0.9 Vander Waals scaling for non polar bonds in the active site of the receptor. These newly designed ligands such as 14 -21 ,23 and 28 have shown good docking scores and predicted activities when compared to already existing ligands MTX and its analogues.